The effectiveness and safety of rituximab as induction therapy in ABO-compatible non-sensitized renal transplantation: A systematic review and meta-analysis of randomized controlled trials - Wisit Cheungpasitporn (2018)
© 2015 © 2015 Taylor & Francis. Background: The objective of this systematic review and meta-analysis was to evaluate the effectiveness and safety of rituximab as induction therapy in ABO-compatible, non-sensitized renal transplantation. Methods: A literature search for randomized controlled trials (RCTs) was performed from inception through February 2015. Studies that reported relative risks or hazard ratios comparing the risks of biopsy-proven acute rejection (BPAR), graft loss, leukopenia, infection or mortality in ABO-compatible, non-sensitized renal transplant recipients who received rituximab as induction therapy versus controls were included. Pooled risk ratios (RRs) and 95% confidence intervals (CIs) were calculated using a random-effect, generic inverse variance method. Results: Four RCTs with 480 patients were included in the meta-analysis. Pooled RR of BPAR in recipients with rituximab induction was 0.90 (95% CI 0.50-1.60). Compared to placebo, the risk of BPAR in rituximab group was 0.76 (95% CI 0.51-1.14, I2 = 0). The risk of leukopenia was increased in rituximab group with the pooled RR of 8.22 (95% CI 2.08-32.47). There were no statistical differences in the risks of infection, graft loss and mortality at 3-6 months after transplantation with pool RRs of 1.02 (95% CI 0.85-1.21), 0.55 (95% CI 0.21-1.48) and 0.58 (95% CI 0.17-1.99), respectively. Conclusion: This meta-analysis demonstrated insignificant reduced risks of BPAR, graft loss or mortality among in ABO-compatible, non-sensitized renal transplant recipients with rituximab induction. Although rituximab induction significantly increases risk of leukopenia, it appears to be safe with no significant risk of infection.